2023
DOI: 10.3390/ijms24098053
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole-Loaded Nanostructured Lipid Carriers for Hyperproliferative Skin Diseases

Abstract: Nanocarriers, and especially nanostructured lipid carriers (NLC), represent one of the most effective systems for topical drug administration. NLCs are biodegradable, biocompatible and provide a prolonged drug release. The glutamate release inhibitor Riluzole (RLZ) is a drug currently used for amyotrophic lateral sclerosis (ALS), with anti-proliferative effects potentially beneficial for diseases with excessive cell turnover. However, RLZ possesses low water solubility and high light-sensibility. We present he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“… [ 92 ] Beeswax, peppermint oil, lavender oil, tween ® 80 <200 nm Hot-pressure homogenization method Riluzole - It can deliver medicine in a sustained manner and inhibit keratinocyte cell proliferation without being angiogenic. [ 93 ] Compritol 888ATO, oleic acid, tween 80, span 20, transcutol P 758 nm Cold homogenization technique Apremilast - It exhibits a slow and sustained release profile, ensuring prolonged maintenance of drug concentration on the skin. [ 94 ] Precirol ATO 5, compritol 888 ATO, stearic acid, glyceryl monostearate, oleic acid, dynasan 114, polysorbate 80 157.91 ± 1.267 nm Hot emulsification technique Apremilast Swiss albino mice It exhibits increased skin retention and reduces TNF-α mRNA expression without inducing toxicity or irritation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 92 ] Beeswax, peppermint oil, lavender oil, tween ® 80 <200 nm Hot-pressure homogenization method Riluzole - It can deliver medicine in a sustained manner and inhibit keratinocyte cell proliferation without being angiogenic. [ 93 ] Compritol 888ATO, oleic acid, tween 80, span 20, transcutol P 758 nm Cold homogenization technique Apremilast - It exhibits a slow and sustained release profile, ensuring prolonged maintenance of drug concentration on the skin. [ 94 ] Precirol ATO 5, compritol 888 ATO, stearic acid, glyceryl monostearate, oleic acid, dynasan 114, polysorbate 80 157.91 ± 1.267 nm Hot emulsification technique Apremilast Swiss albino mice It exhibits increased skin retention and reduces TNF-α mRNA expression without inducing toxicity or irritation.…”
Section: Discussionmentioning
confidence: 99%
“… 92 The optimized NLC loaded with riluzole exhibited optimal properties for dermal application, inhibiting keratinocyte proliferation and enabling sustained drug delivery. 93 Madan, J.R.et al formulated NLCs by a cold homogenization technique using Compritol 888ATO, oleic acid, Tween 80 and Span 20, and Transcutol P as a solid lipid, liquid lipid, surfactant mixture, and penetration enhancer, respectively. Containing Apremilast (APM) for topical application.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they exhibited non-angiogenic properties and impeded keratinocyte cell proliferation. Thus, the NLC containing riluzole and natural essential oils proved to be a favorable approach against hyperproliferative diseases of keratinocytes, such as PSO [ 106 ].…”
Section: Current Nanotechnology-based Approaches For the Topical Trea...mentioning
confidence: 99%
“…Riluzole is a clinical drug approved by the Food and Drug Administration (FDA) for amyotrophic lateral sclerosis due to its neuroprotective and anticonvulsive activities. , Because of its capability to block the pathological intracellular influx of sodium as well as calcium ions and reduce excess Glu in CNS, multiple studies have demonstrated that riluzole has significant neuroprotective effects in the management of acute SCI, and clinical phase 2 and phase 3 trials have been conducted. Although riluzole is considered as a promising neuroprotective agent for SCI, its poor water solubility, short half-life, and potential toxicity to organs such as the liver and kidney at high concentrations have also raised significant concerns. To improve the bioavailability of riluzole, several nanocarriers have been applied to load riluzole and enhance its neuroprotective effect. Nevertheless, the lower tissue accumulation, limited loading efficiency, and polymer/carrier toxicity of these nanocarriers, as well as their performance in response to the microenvironment, remained inadequate for the treatment of SCI. , …”
Section: Introductionmentioning
confidence: 99%